Vocabulary learning strategies among University Science Islamic Malaysia (USIM) Mandarin learner / Yee Chin Yip - Yee, Chin Yip (Universiti Teknologi MARA Perak, 2021)
The present study examined Mandarin vocabulary size and vocabulary learning strategies of University Science Islam Malaysia's (USIM) Level 3 learners. The questionnaire has divided into three sections; firstly, Vocabulary Size Test (VST) was conducted to examine the learners' vocabulary size. The second section was aimed to investigate vocabulary learning strategies applied by the learners. The third section was meant to determine the popular ways under each vocabulary learning strategy. The finding of present study revealed that most Mandarin language learners settled with an unsatisfactory vocabulary size of 200 to 400. Besides that, these express the part where the learners employed cognitive strategies the most and metacognitive strategies the least. Among the most famous strategies include taking notes, revision of words, discuss with classmates, and review vocabulary. The results of this study clearly suggest that training of systematic vocabulary learning strategies should be introduced to assist learners enhance their Mandarin vocabulary size. In addition, the initiative to utilise the learning strategies preferred by learners is also needed in order to increase their vocabulary size and knowledge respectively.